Administrative Strategies to Develop Innovators Among Secondary Science Teachers at Saint Gabriel’s Foundation, Thailand - Kaewyongphang, Phongtorn; Manokarn, Monnapat; Yaboonthong, Yongyouth (Community and Social Development Journal, 2024)
The purposes of the research Administrative Strategies to Develop Innovators Among Secondary Science Teachers at Saint Gabriel’s Foundation, Thailand were to 1) create administrative strategies, 2) validate suitability and feasibility of administrative strategies to develop innovators among secondary science teachers at Saint Gabriel’s Foundation, Thailand. In this research, a mixed method was applied. The data has been gathered from 11 secondary school directors, 110 staff at the management level and 149 secondary science teachers at Saint Gabriel’s Foundation, Thailand in the academic year 2020; there were 270 personnel in total. The tools used to collect the data were questionnaires, interview forms, and focus group forms. The quantitative data was analyzed by using percentage, frequency, mean and standard deviation, whereas content analysis was used to analyze qualitative data. The results of administrative strategies to develop innovators among secondary science teachers at Saint Gabriel’s Foundation, Thailand consisted of vision, missions, goals, share values and 4 master strategies, 13 minor strategies, 28 measures, and 24 indicators. The master strategies were Strategies 1: Encourage and enhance science teachers to be innovation teachers containing 4 minor strategies, 10 measures, and 10 indicators, Strategies 2: Improve quality of science learning management to create innovation consisting of 3 minor strategies, 6 measures, and 4 indicators, Strategy 3: Create cooperative network for creative innovations containing 3 minor strategies, 7 measures, and 5 indicators, and Strategy 4: Effective management of innovative teachers comprising 3 minor strategies, 5 measures, and 5 indicators. Furthermore, the overview result of accuracy and feasibility validation of administrative strategies to develop innovators among secondary science teachers at Saint Gabriel’s Foundation, Thailand was in high average.